2002
DOI: 10.1046/j.1523-1747.2002.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Skin Capillary Density During Attacks of Erythromelalgia Implies Arteriovenous Shunting as Pathogenetic Mechanism

Abstract: Erythromelalgia is characterized by burning pain, erythema, and increased temperature in acral skin. The pain is aggravated by warming and relieved by cooling. Increased microvascular arteriovenous shunting in deep dermal plexa has been hypothesized as the pathogenetic mechanism of pain in affected skin, inducing hypoxia during pain attacks. The aim of this study was to quantify skin capillary density in erythromelalgic patients before and after heat provocation, as increased skin temperature should increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 17 publications
4
57
0
Order By: Relevance
“…In a prospective study, Kalgaard et al (15) reported histopathological findings characterized by capillary proliferation or vascular damage in 31 of 49 specimens, mainly from patients with PEM. These nonspecific alterations indicated the presence of skin hypoxia secondary to increased arteriovenous shunting and insufficient capillary flow, which is compatible with the shunting hypothesis supported by Mørk et al (13,14).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a prospective study, Kalgaard et al (15) reported histopathological findings characterized by capillary proliferation or vascular damage in 31 of 49 specimens, mainly from patients with PEM. These nonspecific alterations indicated the presence of skin hypoxia secondary to increased arteriovenous shunting and insufficient capillary flow, which is compatible with the shunting hypothesis supported by Mørk et al (13,14).…”
Section: Discussionsupporting
confidence: 86%
“…According to the shunting hypothesis, EM symptoms are caused by tissue hypoxia, which is induced by a maldistribution of skin microvascular blood flow with increased thermoregulatory flow through arteriovenous shunts and an inadequate nutritive perfusion to normal skin capillaries (13,14). If available blood is shunted away from normal skin capillaries, the skin will be hypoxic.…”
Section: Discussionmentioning
confidence: 99%
“…15 While the alteration of the sympathetic neurons' function leads to the microvascular symptoms, the alteration of the nociceptive neurons' function results in severe burning pain, characterizing erythromelalgia. 10 Despite an increase blood flow (as measured with laser Doppler), there is local hypoxia that can be reflected by low TCPO 2 values, which might be explained by 29 Unlike the primary type, secondary type pathophysiology is poorly understood and thought to be due to neuropathological and microvascular functional changes caused by the underlying condition. 30 Since there is no diagnostic test for erythromelalgia, a very good history and physical exam are crucial for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The skin, and the dermis in particular, is a very active part of both the antigen-specific and innate immune system that can interfere with the metastatic process. On the other hand, the skin is one of the most capillarized tissues in humans with a density of 70-90 capillaries per mm 2 [31,32]. Considering the spatial limits of oxygen and nutrient diffusion (around 100 μm), disseminated cancer cells in the skin do not depend on their own angiogenic potential.…”
Section: Blood Perfusion Ratementioning
confidence: 99%
“…Reports on the comparison of early and late stage disease CTC numbers found limited correlation [36,37]. With advances of cell isolation technologies, the detection threshold has become lower, reaching 1-5 CTC/10 ml blood [32]. It is a well-established fact that the metastatic efficiency of hematogenous dissemination is 0.01 %; in other words, 1 cell out of 10,000 tumor cells in the circulation [6,7], indicating that the overwhelming majority of CTC is incapable of colonizing the distant organs.…”
Section: Circulating Cancer Cellsmentioning
confidence: 99%